Importance of rivers in the environmental environment - Campoblanco Díaz, Honorio (2000)
Rivers are a system of linear , vector movement , hierarchical and structured to move sediment and vital fluids through the Watershed and mouths , making complex dynamics , mechanical , energy , chemical and biochemical reactions in order to give support in all its route to life in its various forms . The river is an integral part of the energy vector Hydrological Water Cycle and walking only land area , interconnecting the upper solid collector ( Glacier ) with the lower solid collector ( Oceans) and said path meets a supreme mission and deploying specialized work selective as erosion, physical attack , chemical, biochemical , complimentary , selection and sedimentation in the basins of deposition such as alluvial fans , rivers , deltas etc . Disruption and pollution of rivers can change and alter the normal flow of Hydrological Water Cycle causing serious disruptions in the climate of the earth, in the isostatic proscesos and conservation of diverse ecosystems . The scarcity of this precious resource can trigger future wars, serious social conflicts of national and international character is further exacerbated with the high growth rate of the world population .